HLA‐DR polymorphisms influence in vivo responses to staphylococcal toxic shock syndrome toxin‐1 in a transgenic mouse model. (15th November 2016) - Krogman, A.; Tilahun, A.; David, C. S.; Chowdhary, V. R.; Alexander, M. P.; Rajagopalan, G.
Abstract: Toxic shock syndrome toxin‐1 (TSST‐1) is a potent superantigen produced by Staphylococcus aureus . In addition to menstrual and nonmenstrual toxic shock syndromes, TSST‐1 is also implicated in the immunopathogenesis of pneumonia, infective endocarditis, neonatal exanthematous disease, and atopic dermatitis among others. Superantigens first bind to major histocompatibility complex (MHC) class II molecules and then activate a large proportion of T cells by cross‐linking their T cell receptor. As binding to MHC class II molecules is a critical step in the robust activation of the immune system by TSST‐1 and other superantigens, polymorphic variations between different HLA‐DR alleles could potentially influence the magnitude of immune activation and immunopathology caused by TSST‐1. As TSST‐1 is highly toxic to humans and given that multiple variations of alleles of HLA‐DR and HLA‐DQ are expressed in each individual, it is difficult to determine how HLA‐DR polymorphisms quantitatively and qualitatively impact immune activation caused by TSST‐1 in humans. However, such investigations can be conducted on transgenic mice lacking all endogenous MHC class II molecules and expressing specific HLA class II alleles. Therefore, transgenic mice expressing different HLA‐DRB1 alleles ( HLA‐DRB1*15:01, HLA‐DRB1*15:02, HLA‐DRB1*03:01, HLA‐DRB1*04:01 ), and sharing HLA‐A1*01:01 chain, were systemically challenged with purified TSST‐1 and multiple immune parameters were assessed. Among the HLA‐DR alleles, mice expressing HLA‐DRB1*15:01 allele elicited a significantly higher serum cytokine/chemokine response; greater splenic T cell expansion and most severe organ pathology. Our study highlights the potential utility of human leukocyte antigen (HLA) transgenic mice in understanding the impact of HLA polymorphisms on the outcomes of diseases caused by TSST‐1 and other superantigens.